Probiotics and their benefits in pediatric patients - Moncayo, Andres Alulema; Enríquez, Stephany; Ambrossi, Mirna Ugarte; Herrera, Johanna Lisbeth Vásquez; Cifuentes, Paul Aguirre; Montes, Paola Montes; Rogel, Ana Ibarra; Huertas, Danela Coral (International Journal of Research in Medical Sciences, 2025)
Respiratory tract diseases are among the most common infections in childhood and adolescence. In recent years, probiotics have emerged as a promising prophylactic and curative alternative for various digestive, mental and respiratory pathologies. This is attributed to the significant influence that the intestinal microbiota exerts on the immune system. Multiple studies indicate that an impact on the microbiota due to external or internal factors leads to an alteration in the immune system. Among their current uses, they are used for the prevention and treatment of respiratory diseases in children. The studies analyzed show that Lactobacillus casei shows better results in preventing upper respiratory diseases than other probiotics, whether combined or alone. However, the duration of administration is unknown. New advances increasingly point to the positive effect that probiotics show in children, especially those who present repetitive viral or bacterial symptoms. Different investigations open doors and excellent results have been obtained with the use of probiotics.